Harmonization of Islam-Sunda in the Wuku Taun Tradition in Cikondang Village - Erti Dinihayati; Ade Priangani (SAMPURASUN, 2023)
In the case of Sundanese society and culture, many Sundanese classmates were born and raised in a Sundanese environment, but no longer recognize Sundanese culture, customs and values. They are more familiar with foreign cultures and civilizations. The new civilization has had a huge influence on culture and the state of society. The values ​​that were previously believed were intimidated by the new values. On the one hand, positive things have given birth to knowledge for education, but on the other hand, Sundanese noble values ​​have faded, because of the interests of immigrants. The clash of values ​​due to evolutionary faults made the Sundanese generation begin to shift. The values ​​and social institutions that were originally considered as Sundanese identity and entities began to be doubted. They feel more valued as 'European humans' in their native form. Even though Sundanese has culture, has customs, has language, the Sundanese should be aware of their nature as Sundanese. This change has also affected traditional Sundanese villages, which have been persistent in maintaining their traditions. The Sundanese people themselves are no longer familiar with the Traditional Village of Kampung Cikondang in the Bandung area, which so far has been used as a place for preserving Sundanese Customs and Culture. For this reason, the role of all groups, the government, through policies that are more directed at cultural or cultural considerations rather than purely economic ones, are needed which are detrimental to a cultural development in the policies formulated, so that traditional enclaves such as Kampung Adat can eventually sustainable. While the community can play a role according to their respective abilities. The method used in this research is qualitative, that is used as a research procedure that produces descriptive data in the form ofwritten or spoken words from observable persons.